A Neonate with Acquired Factor VII Deficiency Successfully Managed with Immunomodulatory Therapy - Alqarni, Nof Saadi (Int J Pediatr Adolesc Med, 2021)
Acquired factor VII deficiency secondary to circulating inhibitors is rare in children but is a potentially life-threatening condition. Such a disease is challenging to diagnose and often difficult to manage. Here, we report on a newborn that presented with a catastrophic intracranial hemorrhage who failed to respond to conventional supportive measures including multiple doses of fresh frozen plasma and factor VII replacement; however, he had a complete correction of prothrombin time 8 h after immunomodulatory therapies in the form of steroid and intravenous immunoglobulin. Such measures helped stabilize his bleeding and allowed urgent neurosurgical intervention.